Arthroscopic Repair of a Type VIII Superior Labrum Anterior Posterior Tear - Michael Nammour MD; Justin W. Arner MD; Ryan Murray MD; James P. Bradley MD (SAGE Publishing, 2023)
Background: Type VIII superior labrum anterior posterior (SLAP) tears are described as SLAP type II tears with posterior extension to the posterior inferior glenohumeral ligament. These tears are a common source of pain, instability, and decreased function in active individuals, particularly overhead or throwing athletes. Indications: Type VIII SLAP tears can cause pain and loss of sports performance, especially in a throwing athlete. This patient is a quarterback and pitcher who had magnetic resonance imaging and arthroscopic evidence of a type VIII SLAP tear with pain and inability to throw at his preinjury level. Technique Description: In the lateral decubitus position, a standard posterior portal is established along with anterior and accessory lateral portals. A type VIII SLAP tear is identified and the arm is taken out of balanced suspension traction and placed in abduction and external rotation which shows displacement of the posterior labrum and peelback of the superior labrum indicating pathologic labral instability. The labrum is then elevated and glenoid prepared to achieve healthy bleeding bone. Tape sutures are then passed around the labrum and placed into a glenoid anchor starting superiorly and continuing the repair posteroinferiorly. Three anchors were placed in the superior labrum using a percutaneous technique, with 2 more placed from the posterior portal to complete the 5-anchor repair. The posterior portal is then closed with a single monofilament suture to prevent a potential stress riser in the capsule. Results: The literature suggests that athletes with type VIII SLAP tears can expect improved functional outcomes and high return to play rates (>90%); however, only 50% to 70% of throwing athletes return to the same level of play. Discussion/Conclusion: Type VIII SLAP tears are an important cause of shoulder pain and dysfunction, particularly in overhead athletes. Arthroscopic repair of type VIII SLAP tears can improve functional outcomes and ability to return to sport; however, throwing athletes experience lower rates of return to previous level. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.